2015
DOI: 10.2967/jnumed.115.166439
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Sex-Specific Changes in Brain Metabolism and Morphology

Abstract: With a large database, we aimed to evaluate sex-specific distinctive changes in brain glucose metabolism and morphology during normal aging using MRI and 18 F-FDG PET. Methods: A total of 963 cognitively healthy adults were included in this study. All subjects completed a medical questionnaire, took the mini-mental state examination, and underwent brain MRI and whole-body 18 F-FDG PET. The MR and PET images were statistically analyzed using 3-dimensional stereotactic surface projection. All images were correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 33 publications
7
54
0
2
Order By: Relevance
“…Fourth, older adult men experience more accelerated gray matter atrophy in the core NREM slow wave generating region of the medial prefrontal cortex (Kakimoto et al, 2016; Murphy et al, 2009), which is the same cortical region in which atrophy predicts the severity of SWA decline in the elderly in general (Figure 5) (Mander et al, 2013). Moreover, older adult males suffer greater reductions in metabolic activity in the medial prefrontal regions similar to the medial prefrontal SWA-source generating regions, implicating a functional impairment that may even precede the greater medial prefrontal gray matter atrophy observed in men (Kakimoto et al, 2016).…”
Section: What Are the Neurobiological Mechanisms Of Age-related Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, older adult men experience more accelerated gray matter atrophy in the core NREM slow wave generating region of the medial prefrontal cortex (Kakimoto et al, 2016; Murphy et al, 2009), which is the same cortical region in which atrophy predicts the severity of SWA decline in the elderly in general (Figure 5) (Mander et al, 2013). Moreover, older adult males suffer greater reductions in metabolic activity in the medial prefrontal regions similar to the medial prefrontal SWA-source generating regions, implicating a functional impairment that may even precede the greater medial prefrontal gray matter atrophy observed in men (Kakimoto et al, 2016).…”
Section: What Are the Neurobiological Mechanisms Of Age-related Sleepmentioning
confidence: 99%
“…Moreover, older adult males suffer greater reductions in metabolic activity in the medial prefrontal regions similar to the medial prefrontal SWA-source generating regions, implicating a functional impairment that may even precede the greater medial prefrontal gray matter atrophy observed in men (Kakimoto et al, 2016). Independently or collectively, these regionally and functionally specific possibilities all lead to falsifiable predictions regarding the mechanisms of gender differences in sleep deterioration in later life.…”
Section: What Are the Neurobiological Mechanisms Of Age-related Sleepmentioning
confidence: 99%
“…In normal subjects, [ 18 F]FDG PET is able to detect a progressive and diffuse reduction of regional consumption of glucose that parallels advancing atrophy (mainly in the frontal, temporal and parietal areas) and age. Even in the absence of cortical atrophy, a progressive reduction of metabolism in the mesial frontal region can be detected, with possible gender differences (Kakimoto et al, 2016). Note the low uptake in the primary visual cortex, which suggests a diagnosis of DLB.…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…For instance, a large [ 18 F]-FDG PET study consisting of 493 men and 470 women spanning 5 decades (32 – 87 years) showed lower metabolism in parietal cortex for men compared to women, while lower metabolism was observed in ventrolateral prefrontal cortex for women compared to men [215]. In a multi-institutional study of nonischemic heart failure, three radiotracers, [ 15 O]-H 2 O, [ 11 C]-palmitate and [ 11 C]-glucose, were used to evaluate myocardial blood flow and metabolism [216].…”
Section: Preclinical Imagingmentioning
confidence: 99%